High-modulus low-thermal-expansion PAI composite material and forming process thereof

Through high modulus, low thermal expansion PAI composite materials and molding processes, the synergistic effects of ultra-chopped carbon fiber, graphite and polytetrafluoroethylene are used to solve the shortcomings of dimensional stability, structural rigidity and frictional properties of PAI materials, and achieve the application needs of high precision, high temperature stability and long life.

CN120554844APending Publication Date: 2025-08-29SHANGHAI XUEFENG PRECISION MACHINERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511004818.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

Existing PAI materials have shortcomings in dimensional stability, structural rigidity and frictional properties, and it is difficult to meet the application needs of high precision, high temperature stability and long life. Especially in the molding of complex special-shaped parts, there are problems such as poor density and high defect rate of molded parts.

Method used

Using high-modulus, low-thermal expansion PAI composite materials, the coordinated use of ultra-chopped carbon fiber, graphite, polytetrafluoroethylene and additives is used to build a non-directional enhanced network and lubrication interface, and combining multi-stage powder premix, preheating, layered loading and high shear pulse disturbance molding processes to achieve high modulus, low thermal expansion and excellent friction performance of the material.

Benefits of technology

It significantly improves the elastic modulus and dimensional stability of the composite material, reduces the thermal expansion coefficient, improves the material's wear life and dynamic coordination stability, and achieves dimensional control accuracy of ±0.01 mm and deformation tolerance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-modulus low-thermal-expansion PAI composite material and a hot press molding process thereof. The composite material is formed by compounding polyamide-imide powder, ultra-short carbon fibers, graphite, polytetrafluoroethylene, a plurality of interface additives, a stabilizer and the like, the length of the carbon fibers does not exceed 1 mm, the particle size of the graphite is controlled to be 5-20 microns, the proportion of key filler is precisely designed, and a high-rigidity, low-expansion and low-friction composite structure framework is cooperatively constructed. And a hot pressing path combining layered filling, staged exhausting, heating and pressurizing and post-curing treatment is adopted in a matched mode, high-density forming of the composite structure can be achieved, the size control precision is effectively improved, and the service life is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastic molding, and in particular to a high-modulus, low-thermal expansion PAI composite material and a molding process thereof. Background Art

[0002] Polyamide-imide (PAI) is a high-performance engineering plastic that combines thermal stability, mechanical properties, and electrical insulation. It is widely used in high-end manufacturing fields such as aerospace, electronic packaging, rail transportation, and semiconductor testing. Traditional PAI products are mostly produced using injection molding or compression molding processes. However, they still have the following prominent issues in terms of dimensional stability, structural rigidity, and friction performance: First, although PAI material has a certain degree of low thermal expansion characteristics, its dimensional change rate is still relatively high under wide temperature and thermal cycle conditions from -40°C to 200°C, making it difficult to meet the geometric stability requirements of high-precision structural parts under thermal loads. It is prone to fitting failure or alignment deviation, which especially affects the reliability of micro-pitch structures such as semiconductor test fixtures and probe holders.

[0003] Secondly, the elastic modulus of traditional PAI composite materials is generally between 3 and 5 GPa, the structural rigidity is insufficient, and compression deformation or creep is prone to occur under high temperature and high load conditions, making it difficult to support stable positioning or thermal mechanical bearing under complex stress fields.

[0004] Thirdly, the original PAI material has a high friction coefficient under dry friction conditions (generally 0.25 to 0.3), and is prone to wear and jamming in the absence of lubrication or in conditions of frequent plugging and unplugging, which limits its service life and stability in high-frequency moving pairs or precision assembly situations.

[0005] In addition, high-filler systems often suffer from poor density and high defect rates in molded parts due to uneven fiber distribution, bubble inclusions, or excessive orientation during injection molding, making them unsuitable for one-step precision manufacturing of complex, special-shaped parts.

[0006] Therefore, there is an urgent need for a PAI-based composite material and its molding process with high modulus, low thermal expansion, excellent friction performance and dense molding characteristics to meet the application requirements of high-end structural parts under high precision, high temperature stability and long life conditions. Summary of the Invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a high modulus and low thermal expansion PAI composite material and a molding process thereof.

[0008] A high modulus and low thermal expansion PAI composite material comprises the following components in parts by weight: Polyamide-imide powder: 45-60 parts; Ultra-short chopped carbon fiber: 30-42 parts; Graphite: 5-10 parts; Polytetrafluoroethylene: 2-6 parts; Interface coupling agent: 0.3-1.0 parts; Dispersant: 0.5-2.0 parts; Stabilizer: 0.2-0.8 parts; Antioxidant: 0.1-0.5 parts; Release agent: 0.2-0.8 parts; The axial length of the ultra-short chopped carbon fiber is ≤1 mm; The particle size of the graphite is 5 to 20 μm.

[0009] Furthermore, the particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, and the thermal curing starting temperature thereof is not lower than 280°C.

[0010] Furthermore, the mass ratio of the ultra-short chopped carbon fiber to the polyamide-imide powder is controlled to be 0.65 to 0.85.

[0011] Furthermore, the mass ratio of the total mass of the graphite and polytetrafluoroethylene to the mass of the ultra-short chopped carbon fibers is controlled to be 0.25 to 0.5.

[0012] Furthermore, the mass ratio of graphite to polytetrafluoroethylene is (1.5-3):1.

[0013] Furthermore, 0.5 to 1.5 parts of a first mixing auxiliary agent of glycidoxysilane and cage-type polysiloxane are added, and the mass ratio of glycidoxysilane to cage-type polysiloxane is 1:0.8 to 1.5.

[0014] Furthermore, 1 to 4 parts by weight of polybutylene terephthalate staple fibers are added, and the length of the polybutylene terephthalate staple fibers is 0.2 to 0.5 mm.

[0015] A molding process for a high modulus and low thermal expansion PAI composite material comprises the following steps: S1: Weigh polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene in proportion and stir to mix evenly; then dry them at a vacuum degree of ≤-0.08 MPa and a temperature of 80°C for 12 h for pretreatment; S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 15-30 minutes. Then, fill the dry powder pretreated in step S1 into the mold in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 1-2 MPa after each layer is filled. S3: The mold is heated to 150-200°C and vented for 1-2 rounds at a pressure of 0.5-1 MPa, with each round maintaining pressure for 2 minutes. S4: Continue heating to 310-350°C at a rate of 30-50°C / min, and perform molding at a molding pressure of 3-10 MPa, with a holding time of 30-90 min; S5: Cooling the mold at a rate of 30-50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 200-260℃ for 2-6 hours.

[0016] Furthermore, in step S1, 0.5 to 1.5 parts of a first mixing aid of glycidoxysilane and cage polysiloxane are added, and the mass ratio of glycidoxysilane to cage polysiloxane is 1:0.8 to 1.5; and 1 to 4 parts by weight of polybutylene terephthalate staple fibers, wherein the length of the polybutylene terephthalate staple fibers is 0.2 to 0.5 mm.

[0017] Furthermore, in the S1 step, the first mixing aid and the polyamide-imide powder are first premixed at 60-90°C and treated at a constant temperature for 30-60 minutes, and then polybutylene terephthalate staple fiber and ultra-short-cut carbon fiber are added in sequence, and the mixture is continued to be mixed at room temperature for 10-20 minutes, and a high shear pulse disturbance with a rotation speed of 3000-6000 rpm and a duration of 3-8 seconds is applied at the end of the mixing stage; finally, graphite and polytetrafluoroethylene are added and continued to be mixed evenly.

[0018] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects: 1. Construct a high modulus and low thermal expansion reinforced network to achieve a double breakthrough in precise dimensional control and structural load-bearing By introducing ultra-short chopped carbon fibers (≤1 mm) as a three-dimensional reinforcement skeleton and synergistically controlling the mass ratio of ultra-short chopped carbon fibers to the polyamide-imide matrix in the range of 0.65 to 0.85, a non-directionally distributed reinforcement network (orientation index less than 0.4) is constructed, effectively increasing the elastic modulus of the composite material to above 5.5 GPa, while controlling the thermal expansion coefficient to 1.4×1 -5 K -1 The following is significantly better than traditional PAI injection molded parts, achieving a dimensional change rate within 0.1% under -40 to 200°C thermal cycling conditions.

[0019] 2. Lubricating fillers work together to build a layered lubrication interface to improve anti-wear life and dynamic fit stability Graphite and PTFE are used in a synergistic ratio of (1.5-3):1, and the ratio of the total mass to carbon fiber is controlled at 0.25-0.5. This can induce the formation of a "oriented graphite microsheet + embedded PTFE microclusters" structure during the hot pressing process, in which graphite constructs a multi-directional lubrication layer in a planar orientation, and PTFE preferentially migrates and distributes in the interface void area, ultimately forming a buffering lubrication composite domain in the interface area of ​​the composite material.

[0020] 3. The additive system builds interface bridge chains and grain confinement structures to enhance structural consistency and thermal aging stability Glycidoxysilane and cage polysiloxane synergistically form the first mixing additive. After being premixed into the PAI matrix, they form stable chemical bonds and organic-inorganic interface bridge chains during hot pressing and post-curing, thereby improving the interfacial wettability and adhesion between carbon fiber, graphite and PAI, inhibiting thermal degradation and microcrack propagation, and giving the material a stronger dimensional memory effect and strength retention after thermal cycling.

[0021] 4. Compound crystal form to regulate fiber reinforcement unit to achieve strong and tough compatibility and high temperature dimensional self-supporting ability Adding 1 to 4 parts of polybutylene terephthalate (PBT) staple fibers (0.2 to 0.5 mm) as a flexible crystalline fiber phase can introduce grain confinement and rigid-flexible transition mechanisms into the PAI / carbon fiber reinforced skeleton, thereby enhancing the deformation tolerance and impact toughness of the structure under complex thermal loads. It is particularly suitable for environments with dynamic thermal vibration and micro-impact loads such as rail transit and electric drive housings.

[0022] 5. The process path accurately controls the spatial distribution of each component to achieve the coordinated construction of dense molding and functional structure The present invention adopts a six-step hot pressing path of multi-stage powder premixing + preheating + layered filling + stage pressurization and exhaust + post-curing, and introduces 3000-6000 rpm high shear pulse disturbance at the end of mixing to effectively break up powder agglomeration and promote the heterogeneous distribution of lubricating fillers and reinforcing fillers, ultimately achieving a microstructure coordinated layout in which graphite and PTFE are segregated at the interface, carbon fibers form a non-directional reinforced skeleton, and PBT short fibers are confined to crystallize in local areas; the compacted density of the obtained material reaches more than 98%, and after hot pressing, the dimensional control accuracy of ±0.01 mm can be achieved without secondary processing. DETAILED DESCRIPTION

[0023] The present invention is described in detail below with reference to the embodiments.

[0024] Example 1 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Graphite: 7.5 parts; Polytetrafluoroethylene: 2.5 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0025] The average axial length of the ultra-short chopped carbon fibers is 0.6 mm; The average particle size of graphite is 10 μm.

[0026] The average particle size of the PTFE powder is 5 μm.

[0027] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0028] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0029] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0030] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0031] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0032] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 30 minutes to ensure full and uniform dispersion. The mixture was then dried for 12 hours under a nitrogen atmosphere at a vacuum degree of –0.08 MPa and a temperature of 80°C for pretreatment. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 30 min. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 2 MPa after each layer is filled. S3: The mold is heated to 200°C and vented for two rounds at a pressure of 1 MPa, with each round holding pressure for 2 minutes. S4: heating to 350°C at 50°C / min, and performing molding at a molding pressure of 10 MPa with a holding time of 90 min; S5: Cooling the mold at a rate of 50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 260°C for 6 hours.

[0033] Example 2 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 35 parts; Graphite: 5.0 parts; Polytetrafluoroethylene: 5.0 parts; Interfacial coupling agent: 0.6 parts; Dispersant: 1.4 parts; Stabilizer: 0.3 parts; Antioxidant: 0.2 parts; Release agent: 0.4 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0034] The average axial length of the ultra-short chopped carbon fibers is 0.6 mm; The average particle size of graphite is 10 μm.

[0035] The average particle size of the PTFE powder is 5 μm.

[0036] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0037] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0038] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0039] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0040] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0041] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 20 minutes to ensure uniformity. The mixture was then dried at a vacuum of –0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0042] Example 3 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 52.5 parts; Ultra-short chopped carbon fiber: 42 parts; Graphite: 6.0 parts; Polytetrafluoroethylene: 2.0 parts; Interfacial coupling agent: 0.7 parts; Dispersant: 1.6 parts; Stabilizer: 0.5 parts; Antioxidant: 0.3 parts; Release agent: 0.4 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0043] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0044] The average particle size of the PTFE powder is 5 μm.

[0045] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0046] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0047] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0048] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0049] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0050] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 20 minutes to ensure uniformity. The mixture was then dried at a vacuum of –0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0051] Example 4 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 60 parts; Ultra-short chopped carbon fiber: 30 parts; Graphite: 6.0 parts; Polytetrafluoroethylene: 2.0 parts; Interfacial coupling agent: 0.4 parts; Dispersant: 1.0 part; Stabilizer: 0.3 parts; Antioxidant: 0.2 parts; Release agent: 0.3 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0052] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0053] The average particle size of the PTFE powder is 5 μm.

[0054] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0055] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0056] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0057] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0058] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0059] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 15 minutes. The mixture was then dried at a vacuum of –0.05 MPa and a temperature of 80°C for 12 hours. During the drying process, a slight airflow was maintained to improve uniformity. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 15 min. Then, the dry powder pretreated in step S1 is loaded into the mold in layers, with each layer being 5 mm thick. After each layer is loaded, a pre-compression treatment of 1 MPa is applied. S3: The mold is heated to 150°C and a round of exhaust treatment is performed at a pressure of 0.5 MPa, with each round of pressure holding for 2 minutes. S4: heating to 310°C at 30°C / min, and performing molding at a molding pressure of 3 MPa, with a holding time of 30 min; S5: Cooling the mold at a rate of 30°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 200°C for 2 h.

[0060] Example 5 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 60 parts; Ultra-short chopped carbon fiber: 30 parts; Graphite: 5.0 parts; Polytetrafluoroethylene: 4.0 parts; Interfacial coupling agent: 0.3 parts; Dispersant: 0.8 parts; Stabilizer: 0.2 parts; Antioxidant: 0.1 part; Release agent: 0.2 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0061] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0062] The average particle size of the PTFE powder is 5 μm.

[0063] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0064] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0065] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0066] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0067] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0068] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 20 minutes to ensure uniformity. The mixture was then dried at a vacuum of –0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0069] Example 6 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Graphite: 7.5 parts; Polytetrafluoroethylene: 2.5 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; First mixing aid: 1.5 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0070] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0071] The average particle size of the PTFE powder is 5 μm.

[0072] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0073] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0074] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0075] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0076] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0077] The first mixing auxiliary agent is a mixture of glycidoxysilane and cage polysiloxane in a mass ratio of 1:1.3.

[0078] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, first mixing aid, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 20 minutes to ensure uniformity. The mixture was then dried at a vacuum of –0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0079] Example 7 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Graphite: 7.5 parts; Polytetrafluoroethylene: 2.5 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; First mixing aid: 1.5 parts; Polybutylene terephthalate staple fiber: 3 parts.

[0080] The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0081] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0082] The average particle size of the PTFE powder is 5 μm.

[0083] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0084] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0085] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0086] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0087] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0088] The first mixing auxiliary agent is a mixture of glycidoxysilane and cage polysiloxane in a mass ratio of 1:1.3.

[0089] The average length of the polybutylene terephthalate staple fibers is 0.5 mm.

[0090] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, the first mixing aid, polybutylene terephthalate staple fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 20 minutes to ensure uniformity. The mixture was then dried at a vacuum of –0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0091] Example 8 A high modulus and low thermal expansion PAI composite material disclosed in this embodiment includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Graphite: 7.5 parts; Polytetrafluoroethylene: 2.5 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; First mixing aid: 1.5 parts; Polybutylene terephthalate staple fiber: 3 parts.

[0092] The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0093] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0094] The average particle size of the PTFE powder is 5 μm.

[0095] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0096] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0097] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0098] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0099] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0100] The first mixing auxiliary agent is a mixture of glycidoxysilane and cage polysiloxane in a mass ratio of 1:1.3.

[0101] The average length of the polybutylene terephthalate staple fibers is 0.5 mm.

[0102] This embodiment also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Premix the first mixing aid with polyamide-imide powder at 80°C and heat for 40 minutes. Then, add polybutylene terephthalate staple fiber and ultra-short carbon fiber in sequence and continue mixing at room temperature for 10-20 minutes. At the end of the mixing, apply a high shear pulse perturbation at 6000 rpm for 3 seconds. Finally, add graphite and polytetrafluoroethylene and continue mixing. Then, dry at a vacuum of -0.06 MPa and a temperature of 80°C for 12 hours, using inert gas to assist in dehumidification. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 22 minutes. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer having a thickness of 7 mm. After each layer is filled, apply a pre-compression treatment of 1.5 MPa. S3: The mold is heated to 175°C and a round of exhaust treatment is performed at a pressure of 0.75 MPa, with each round of pressure holding for 2 minutes. S4: heating to 330°C at 40°C / min, and performing molding at a molding pressure of 6 MPa, with a holding time of 60 min; S5: Cooling the mold at 40°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 230°C for 4 hours.

[0103] Comparative Example 1 A high modulus, low thermal expansion PAI composite material disclosed in this comparative example includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Carbon fiber: 40 parts; Graphite: 7.5 parts; Polytetrafluoroethylene: 2.5 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0104] The average axial length of carbon fibers is 6 mm; The average particle size of graphite is 10 μm.

[0105] The average particle size of the PTFE powder is 5 μm.

[0106] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0107] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0108] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0109] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0110] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0111] This comparative example also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 30 minutes to ensure full and uniform dispersion. The mixture was then dried for 12 hours under a nitrogen atmosphere at a vacuum degree of –0.08 MPa and a temperature of 80°C for pretreatment. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 30 min. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 2 MPa after each layer is filled. S3: The mold is heated to 200°C and vented for two rounds at a pressure of 1 MPa, with each round holding pressure for 2 minutes. S4: heating to 350°C at 50°C / min, and performing molding at a molding pressure of 10 MPa with a holding time of 90 min; S5: Cooling the mold at a rate of 50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 260°C for 6 hours.

[0112] Comparative Example 2 A high modulus, low thermal expansion PAI composite material disclosed in this comparative example includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Polytetrafluoroethylene: 10 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0113] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of the PTFE powder is 5 μm.

[0114] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0115] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0116] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0117] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0118] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0119] This comparative example also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 30 minutes to ensure full and uniform dispersion. The mixture was then dried for 12 hours under a nitrogen atmosphere at a vacuum degree of –0.08 MPa and a temperature of 80°C for pretreatment. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 30 min. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 2 MPa after each layer is filled. S3: The mold is heated to 200°C and vented for two rounds at a pressure of 1 MPa, with each round holding pressure for 2 minutes. S4: heating to 350°C at 50°C / min, and performing molding at a molding pressure of 10 MPa with a holding time of 90 min; S5: Cooling the mold at a rate of 50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 260°C for 6 hours.

[0120] Comparative Example 3 A high modulus, low thermal expansion PAI composite material disclosed in this comparative example includes the following components in parts by weight: Polyamide-imide powder: 50 parts; Ultra-short chopped carbon fiber: 40 parts; Graphite: 10 parts; Interfacial coupling agent: 0.5 parts; Dispersant: 1.5 parts; Stabilizer: 0.5 parts; Antioxidant: 0.2 parts; Release agent: 0.5 parts; The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, the average particle size is 60 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

[0121] The average axial length of the ultra-short chopped carbon fiber is 0.6 mm; The average particle size of graphite is 10 μm.

[0122] The interfacial coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0123] The dispersant is a high temperature stable polyether modified polyester dispersant (BYK-9076).

[0124] The stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0125] The antioxidant was antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).

[0126] The demoulding aid is high-temperature silicone oil-coated silica powder.

[0127] This comparative example also discloses a molding process of the high modulus and low thermal expansion PAI composite material, which specifically includes the following steps: S1: Polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene were weighed in proportion and stirred for 30 minutes to ensure full and uniform dispersion. The mixture was then dried for 12 hours under a nitrogen atmosphere at a vacuum degree of –0.08 MPa and a temperature of 80°C for pretreatment. S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 30 min. Then, fill the mold with the dry powder pretreated in step S1 in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 2 MPa after each layer is filled. S3: The mold is heated to 200°C and vented for two rounds at a pressure of 1 MPa, with each round holding pressure for 2 minutes. S4: heating to 350°C at 50°C / min, and performing molding at a molding pressure of 10 MPa with a holding time of 90 min; S5: Cooling the mold at a rate of 50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 260°C for 6 hours.

[0128] Detection method 1. Tensile modulus test According to the standard GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the tensile modulus of the composite materials of each embodiment and comparative example was tested. 2. Thermal expansion coefficient test According to the standard GB / T 36800.2-2018 “Thermomechanical Analysis of Plastics (TMA) Part 2: Determination of Linear Thermal Expansion Coefficient and Glass Transition Temperature”, the thermal expansion coefficient of the composite materials of various examples and comparative examples was tested.

[0129] 3. Dry friction coefficient and wear rate test According to GB / T 3960-2016, "Test Method for Sliding Friction and Wear Properties of Plastics," the dry friction coefficient of the composite materials of each embodiment and comparative example was tested. The volume change (ΔV) of the specimen before and after wear was also measured. The wear rate W was calculated based on the sliding distance (L) and the normal force (N): The unit is usually mm³ / (N·m), and the smaller the value, the better the wear resistance.

[0130] 1. Thermal aging strength retention test The heat aging strength retention rate of the composite materials of various examples and comparative examples was tested according to GB / T 7141-2008 “Test methods for thermal aging of plastics”.

[0131] 2. Dimensional change rate test Standard rectangular blocks of the composite materials from each example and comparative example were prepared. The initial length L0, width W0, and height H0 were recorded. After 50 cycles of thermal cycling (–40°C to 200°C, heating at 5°C per minute, with each temperature step held for 5–10 minutes), the final dimensions L1 / W1 / H1 were measured at room temperature. The dimensional change rates in each direction were calculated as follows: The maximum value of dimensional changes in three directions is used to express dimensional stability.

[0132] The test results of all the above tests are shown in Tables 1 and 2 below.

[0133] Table 1 Table 2 The above are merely preferred embodiments of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions based on the principles of the present invention are within the scope of protection of the present invention. It should be noted that improvements and modifications that do not depart from the principles of the present invention are within the scope of protection of the present invention.

Claims

1. A high modulus and low thermal expansion PAI composite material, characterized in that: The composition comprises the following components in parts by weight: Polyamide-imide powder: 45-60 parts; Ultra-short chopped carbon fiber: 30-42 parts; Graphite: 5-10 parts; Polytetrafluoroethylene: 2-6 parts; Interface coupling agent: 0.3-1.0 parts; Dispersant: 0.5-2.0 parts; Stabilizer: 0.2-0.8 parts; Antioxidant: 0.1-0.5 parts; Release agent: 0.2-0.8 parts; The axial length of the ultra-short chopped carbon fiber is ≤1 mm; The particle size of the graphite is 5 to 20 μm.

2. The high modulus, low thermal expansion PAI composite material according to claim 1, characterized in that: The particle size distribution of the polyamide-imide powder is controlled to be 20-80 μm, and the thermal curing starting temperature thereof is not lower than 280° C.

3. The high modulus, low thermal expansion PAI composite material according to claim 1, characterized in that: The mass ratio of the ultra-short chopped carbon fibers to the polyamide-imide powder is controlled to be 0.65 to 0.

85.

4. The high modulus, low thermal expansion PAI composite material according to claim 1, characterized in that The mass ratio of the total mass of the graphite and polytetrafluoroethylene to the mass of the ultra-short chopped carbon fibers is controlled to be 0.25-0.

5.

5. The high modulus, low thermal expansion PAI composite material according to claim 1, characterized in that: The mass ratio of graphite to polytetrafluoroethylene is (1.5~3):

1.

6. The high modulus, low thermal expansion PAI composite material according to claim 1, characterized in that: 0.5 to 1.5 parts of a first mixing auxiliary agent of glycidoxysilane and cage-type polysiloxane are also added, and the mass ratio of glycidoxysilane to cage-type polysiloxane is 1:0.8 to 1.

5.

7. The high modulus, low thermal expansion PAI composite material according to claim 6, characterized in that: 1 to 4 parts by weight of polybutylene terephthalate staple fibers are also added, and the length of the polybutylene terephthalate staple fibers is 0.2 to 0.5 mm.

8. A molding process for the high modulus and low thermal expansion PAI composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Weigh polyamide-imide powder, ultra-short carbon fiber, graphite, and polytetrafluoroethylene in proportion and stir to mix evenly; then dry them at a vacuum degree of ≤-0.08 MPa and a temperature of 80°C for 12 h for pretreatment; S2: Apply a release agent evenly to the mold surface and preheat at 200°C for 15-30 minutes. Then, fill the dry powder pretreated in step S1 into the mold in layers, with each layer no thicker than 10 mm. Apply a pre-compression treatment of 1-2 MPa after each layer is filled. S3: The mold is heated to 150-200°C and vented for 1-2 rounds at a pressure of 0.5-1 MPa, with each round maintaining pressure for 2 minutes. S4: Continue heating to 310-350°C at a rate of 30-50°C / min, and perform molding at a molding pressure of 3-10 MPa, with a holding time of 30-90 min; S5: Cooling the mold at a rate of 30-50°C / min to below 150°C, followed by pressure relief and demoulding; after demoulding, the mold is naturally cooled to room temperature to obtain a molded part; S6: Place the molded part in a thermal cycle oven and keep it at 200-260℃ for 2-6 hours.

9. The high modulus, low thermal expansion PAI composite material according to claim 8, characterized in that: In step S1, 0.5 to 1.5 parts of a first mixing aid of glycidoxysilane and cage polysiloxane are added, the mass ratio of glycidoxysilane to cage polysiloxane being 1:0.8 to 1.5; and 1 to 4 parts by weight of polybutylene terephthalate staple fibers, wherein the length of the polybutylene terephthalate staple fibers is 0.2 to 0.5 mm.

10. The high modulus, low thermal expansion PAI composite material according to claim 9, characterized in that: In the S1 step, the first mixing aid and the polyamide-imide powder are premixed at 60-90°C and treated at a constant temperature for 30-60 minutes, and then polybutylene terephthalate staple fiber and ultra-short-cut carbon fiber are added in sequence, and the mixture is continued to be mixed at room temperature for 10-20 minutes. At the end of the mixing, a high shear pulse disturbance with a rotation speed of 3000-6000 rpm and a duration of 3-8 seconds is applied; finally, graphite and polytetrafluoroethylene are added and continued to be mixed evenly.

Citation Information

Patent Citations

  • Carbon fiber reinforced polyimide composite material and preparation method thereof

    CN103483816A

  • Polyimide friction material for rotary ultrasonic motor and preparation method of polyimide friction material

    CN103911118A

  • High-temperature-resistant polyimide composite material and preparation method thereof

    CN112812558A

  • Polyimide composite material and preparation method thereof

    CN113683887A

  • Thermoplastic resin composition and manufacturing method therefor

    JP2019172723A